POLA KOMUNIKASI BUDAYA DALAM TRADISI PERKAWINAN PADA MASYARAKAT BUGIS KABUPATEN PANGKEP - Khatima , Husnil; hadawiah, hadawiah; F. Amin , Kasma (UNIVERSITAS MUSLIM INDONESIA, 2022)
The aims of this research are: (1) How is the Traditional Marriage Process of the Bugis Society in Pangkep Regency. (2) What is the Meaning of the Marriage Tradition of the Bugis Society of Pangkep Regency. (3) How is the Communication Pattern on the Marriage Customs of the Bugis Community in Pangkep Regency.This research lasted for one month and was located in the Pangkep Regency area. precisely in the Padanglampe Village with (6) six informants of which they were people from Pangkep Regency. The research method used is a qualitative research method. with data collection techniques carried out in two ways. namely primary data and secondary data. The data collection method is by conducting observations. interviews. documentation. literature studies and phenomenological methods.The results show that the Bugis community marriage process in Pangkep district has three stages. the first stage before marriage there are 5 traditions. the second stage of marriage there are 5 traditions then the post-wedding stage there are 2 traditions. in that tradition certainly saves some deep meanings. and there are also elements of primary and circular communication patterns.